Use of hydroxyurea in sickle cell anemia: a literature review (Research, Society and Development, 2020)
Hydroxyurea (HU) is the most important advance in the treatment of patients with sickle cell disease (SCD). Sickle cell disease is a debilitating and hereditary disease most common in Brazil and worldwide, with a predominance of black people. The aim of this study was to analyze the importance, benefits and adverse reactions of using hydroxyurea in the treatment of sickle cell anemia through a literature review. The research was conducted through bibliographic analysis by the literature review method performed in the Latin American and Caribbean Health Sciences Information System (LILACS), Scientific Electronic Library Online (SCIELO) databases. The following descriptors were used to survey the articles: Hydroxyurea, Sickle Cell Anemia, Sickle Cell Disease, articles published between 2006 and 2016 in Portuguese language were selected. Thus, 13 articles, through content analysis, were built four analytical categories: Characterization of sickle cell anemia, Benefits expected in the treatment with the use of UH, Criteria used for treatment with UH, Adverse reactions to UH. UH brings a quality of life for the patient as it reduces the number of hospitalizations and length of stay, decreases blood transfusions, reduces painful crises and occurrences of Acute Thoracic Syndrome (STA), minimizes splenic seizures and possible seizures. acute neurological events, generates regression or stabilization of organ damage, reducing the mortality of these patients by up to 40%.